Development of Simulator Guidelines for Resident Assessment in Flexible Endoscopy. Issue 1 (January 2013) - Sutton, Erica; Chase, Sheree Carter; Klein, Rosemary; Zhu, Yue; Godinez, Carlos; Youssef, Yassar; Park, Adrian
Virtual reality (VR) simulators may hold a role in the assessment of trainee abilities independent of their role as instructional instruments. Thus, we piloted a course in flexible endoscopy to surgical trainees who had met Accreditation Council for Graduate Medical Education endoscopy requirements to establish the relationship between metrics produced by a VR endoscopic simulator and trainee ability. After a didactic session, we provided faculty instruction to senior residents for Case 1 upper endoscopy and colonoscopy modules on the CAE Endoscopy VR. Course conclusion was defined as a trainee meeting all proficiency standards in basic endoscopic procedures on the simulator. Simulator metrics and course evaluation comprised data. Eleven and eight residents participated in the colonoscopy and upper endoscopy courses, respectively. Average time to reach proficiency standards for esophagogastroduodenoscopy was 6 and 13 minutes for colonoscopy after a median of one (range, one to two) and one (range, one to four) task repetitions, respectively. Faculty instruction averaged 7.5 minutes of instruction per repetition. A subjective course evaluation demonstrated that the course improved learners' knowledge of the subject and comfort with endoscopic equipment. Within a VR-based curriculum, experienced residents rapidly achieved task proficiency. The resultant scores may be used as simulator guidelines for resident assessment and readiness to perform flexible endoscopy.